1996
DOI: 10.1007/bf01806809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic urokinase inhibitors on local invasion and metastasis in a murine mammary tumor model

Abstract: Urokinase-type plasminogen activator (uPA) initiates an extracellular proteolytic cascade with which invasive cells eliminate barriers to movement. We have evaluated the antiinvasive and antimetastatic properties of two recently developed synthetic uPA inhibitors, B428 and B623, in a BALB/c mouse mammary carcinoma model. We used the F3II and M3 tumor cell lines, previously described by our laboratory. In vitro, noncytotoxic concentrations of B428 or B623 inhibited secreted and cell-associated uPA activity prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…We had previously found, in coincidence with the present results, that MM3 tumor secretes about 3-to 4-fold more uPA than M3 (14). Furthermore, the critical role of uPA in the invasive phenotype of this mammary tumor model was also demonstrated in vivo (31). The present analysis revealed that several members of the TGFßs/TßRs system [TGFß2, TGFß receptor 1 (TßR-1), TGFß receptor type III] were coordinately upregulated in MM3 adenocarcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…We had previously found, in coincidence with the present results, that MM3 tumor secretes about 3-to 4-fold more uPA than M3 (14). Furthermore, the critical role of uPA in the invasive phenotype of this mammary tumor model was also demonstrated in vivo (31). The present analysis revealed that several members of the TGFßs/TßRs system [TGFß2, TGFß receptor 1 (TßR-1), TGFß receptor type III] were coordinately upregulated in MM3 adenocarcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…Secreted tumor-derived protease activity was investigated in conditioned media, as reported (Alonso et al, 1996a). Semiconfluent tumor cells grown in 24-well plates were cultured for 24 hr in MEM plus 5% FBS, in the presence and the absence of paclitaxel (4 µM) or nocodazole (1 µM).…”
Section: Preparation Of Conditioned Mediamentioning
confidence: 99%
“…The radial caseinolytic assay, using plasminogen-rich caseinagarose plates, described by Saksela (1981), was employed to quantify uPA activity in conditioned media, as described in detail (Alonso et al, 1996a). Secreted uPA activity was referenced to a standard urokinase curve (0.2 to 50 IU/ml) and normalized to 10 6 cells and to a 24-hr or 1-hr incubation period.…”
Section: Radial Caseinolytic Assaymentioning
confidence: 99%
“…In addition, studies performed with both in vitro and in vivo experimental models have demonstrates that the levels of uPA are closely associated with the degree of tumor cell invasion (Xing et al, 1996). Blocking uPA expression or disruption of uPA binding to uPAR has been found to significantly inhibit tumor cell invasion and metastasis in various tumor models (Alonso et al, 1996;Kriiger et al, 2000). From these facts, it is apparent that uPA plays a key role in tumor progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%